THE EFFECT OF CONFLICT MANAGEMENT AND WORKLOAD ON NURSES' PERFORMANCE - Putri Riskina; Putri Tia Novita; Fauziah Fauziah; Arista Ardilla; Rauzatul Jannah (Getsempena Health Science Journal, 2025)
Performance is a situation of factors related to work, interacting with factors from within the individual and changing physiological and psychological conditions so that the condition deviates from normal. The purpose of this study is to determine the Effect of Conflict Management and Workload on Nurse Performance at Cut Mutia Regional General Hospital, North Aceh Regency. This type of research is quantitative research with a cross-sectional approach. The population in this study were 37 nurses at Cut Mutia Regional General Hospital. Sampling was carried out using the total sampling method. Based on the results of the linear regression test on conflict management, the p value was obtained = 0.002 and on workload, the p value was obtained = 0.000 <α 0.05 and with the level of influence that there is an influence. This shows that the ρ value <α then the hypothesis Ha is accepted and Ho is rejected which means "there is an influence of conflict management and workload on nurse performance at Cut Mutia Regional General Hospital, North Aceh Regency". This means that conflict management and workload affect nurse performance. Especially nurses at the Cut Mutia Health Center are expected to be more careful in their work, so they can identify problems and fix problems that occur.